2017
DOI: 10.3390/en10040490
|View full text |Cite
|
Sign up to set email alerts
|

Research and Application of Hybrid Forecasting Model Based on an Optimal Feature Selection System—A Case Study on Electrical Load Forecasting

Abstract: Abstract:The process of modernizing smart grid prominently increases the complexity and uncertainty in scheduling and operation of power systems, and, in order to develop a more reliable, flexible, efficient and resilient grid, electrical load forecasting is not only an important key but is still a difficult and challenging task as well. In this paper, a short-term electrical load forecasting model, with a unit for feature learning named Pyramid System and recurrent neural networks, has been developed and it c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…Today, MTLF is a method used in the smart grid for electricity price and load forecasting, although it has not gained full explorations. Contrarily, STLF is widely studied in [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 24 ], which imperatively introduce competitiveness in the electricity markets. Several methods of load forecasting begin from the conventional time series analysis to computational intelligence such as machine learning.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Today, MTLF is a method used in the smart grid for electricity price and load forecasting, although it has not gained full explorations. Contrarily, STLF is widely studied in [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 24 ], which imperatively introduce competitiveness in the electricity markets. Several methods of load forecasting begin from the conventional time series analysis to computational intelligence such as machine learning.…”
Section: Related Workmentioning
confidence: 99%
“…The accuracy of the proposed forecasting model is examined using cumulative variation of root mean square error (RMSE) and mean absolute percentage error. Dong et al [ 13 ] demonstrated STLF via a unit feature learning known as pyramid system and recurrent neural network (PRNN). The proposed system provides security and stability of the power grid.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This model can significantly enhance the effectiveness of power load forecast. Dong, Y. et al [26] developed a short-term load prediction model using a unit for feature learning named Pyramid System and recurrent neural networks, and it can greatly increase the stabilization and safety of the smart grid. Wang, R. et al [27] proposed a new power load forecasting system by combining data preprocessing, hybrid optimized algorithm and certain individual conventional prediction methods, which conquers the shortcomings of individual conventional prediction model and obtains a single model optimization with higher prediction accuracy than traditional forecasting model.…”
Section: Introductionmentioning
confidence: 99%
“…Since estimating the electricity demand becomes harder as the planning horizon increases, the predictions can be strongly influenced by several nonuniform variables such as electric consumption, temperature, air humidity, and socioeconomic aspects. Moreover, long-and regular-term time series make the problem more difficult to be technically managed and solved, as obtaining a computationally robust solution to act in real scenarios requires the integration of customized tuning approaches and non-linear models as a unified framework to properly work [15][16][17][18][19]. Therefore, in this paper, our main interest lies in designing well-behaved forecasters to assess and predict the electricity demand in Brazil for both long-and regular-term time series.Considering the recent advances in Machine Learning (ML) for electricity load forecasting, the literature offers a variety of approaches, most of them specifically designed to solve a particular case study of energy consumption.…”
mentioning
confidence: 99%